CCBE1 in Cardiac Development and Disease - Bonet, Fernando; Inácio, José M.; Bover, Oriol; Añez, Sabrina B.; Belo, José A. (Frontiers in Genetics, 2022)
The collagen- and calcium-binding EGF-like domains 1 (CCBE1) is a secreted protein extensively described as indispensable for lymphangiogenesis during development enhancing VEGF-C signaling. In human patients, mutations in CCBE1 have been found to cause Hennekam syndrome, an inherited disease characterized by malformation of the lymphatic system that presents a wide variety of symptoms such as primary lymphedema, lymphangiectasia, and heart defects. Importantly, over the last decade, an essential role for CCBE1 during heart development is being uncovered. In mice, Ccbe1 expression was initially detected in distinct cardiac progenitors such as first and second heart field, and the proepicardium. More recently, Ccbe1 expression was identified in the epicardium and sinus venosus (SV) myocardium at E11.5–E13.5, the stage when SV endocardium–derived (VEGF-C dependent) coronary vessels start to form. Concordantly, CCBE1 is required for the correct formation of the coronary vessels and the coronary artery stem in the mouse. Additionally, Ccbe1 was found to be enriched in mouse embryonic stem cells (ESC) and revealed as a new essential gene for the differentiation of ESC-derived early cardiac precursor cell lineages. Here, we bring an up-to-date review on the role of CCBE1 in cardiac development, function, and human disease implications. Finally, we envisage the potential of this molecule’s functions from a regenerative medicine perspective, particularly novel therapeutic strategies for heart disease.